THE INFLUENCE OF VEGETABLE FARMERS' PERCEPTIONS AND INTERESTS ON THE DECISION TO USE FINANCIAL TECHNOLOGY IN PASIRWANGI SUBDISTRICT, GARUT DISTRICT - Ega Putri Salsabila; Tuti Karyani (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Vegetable commodities have the potential and play an active role in contributing to GDP (Gross Domestic Product). West Java, Garut Regency is a district that is dominant in producing vegetable commodities where one of its central sub-districts is Pasirwangi. The basic problem that is often faced by the agricultural sector is capital, farmers in Pasirwangi Subdistrict also face the same thing. The presence of financial technology as a technology is expected to facilitate farmer capital and encourage the advancement of modern agricultural financing technology. This study aims to describe the perceptions and interests of vegetable farmers towards financial technology and to analyze the influence of these variables on the decision to use. The research was conducted in Pasirwangi Subdistrict with 60 respondents. The research design uses a quantitative research design and survey methods. The data analysis used is descriptive analysis and multiple linear regression. The results of the study show that farmers have a fairly good perception and interest in financial technology, this is assessed from the answers to each indicator. Farmers' perceptions and interests are classified as significant so that they have an influence on the decision to use financial technology.